PANTANG LARANG DALAM FENOMENA SOSIAL MASYARAKAT MELAYU - Syah, Efrizal Amarullah (Universitas Lancang Kuning, 2011)
Malay culture in Riau is influenced by various elements. The influence affects on Malay tradition, one of them is a tradition called